Possible genetic heterogeneity in X linked hypohidrotic ectodermal dysplasia. Issue 7 (July 1990) - Goodship, J; Malcolm, S; Clarke, A; Pembrey, M E
Abstract : Hypohidrotic ectodermal dysplasia has been mapped to Xq11-q13 by linkage studies and by a translocation in a manifesting female. We report a family with hypohidrotic ectodermal dysplasia in which the disease did not segregate with this region of the X chromosome as expected. Ten DNA probes which are localised between Xp11 and Xq22 were used in the investigation. The difficulties in diagnosing the carrier state in this condition and the possibility of non-allelic heterogeneity are discussed.